(untitled) (Journal of Engineering, 2024)
When designing the pavement layers, a suitable thickness must be chosen to protect the pavement from environmental conditions and traffic loads and ensure the structure’s durability up to the design life. To investigate the behavior of flexible pavement, the characteristics and thickness of each layer are programmed into the finite element method (FEM). The Abaqus program is one of the infinite-element analysis programs. The use of the Abaqus program leads to a reduction in cost and time compared to laboratory tests. In this study, the Abaqus program analyzed a three-dimensional model of a multi-layered road section, and all materials have elastic behavior. The model comprises five layers (wearing, binder, base, subbase, and subgrade). The model was looked at with different base layer thicknesses (15, 25, and 30 cm) and elasticity moduli (1655, 2070, and 3000 MPa). Critical parameters were looked at in the present research: vertical displacement at the wearing layer’s top, horizontal tensile strain in the asphalt layer’s lowest point, and vertical compressive strain at the subgrade’s surface. The outcomes indicated that the pavement is more susceptible to rutting than fatigue as a result of static load. An increase in thickness and modulus of elasticity for the base layer leads to a reduction in rutting risks.